The Effect of Employee Stock Option (ESOs) on Abnormal Returns in Companies Listed Indonesia Stock Exchange: Corporate Governance as Moderating - RIZAL, Syamsul; ISMAIL; BADARUDDIN (Indonesian Journal Economic Review (IJER), 2021)
This study aims to determine the effect of Employee Stock Options (ESOs) on Abnormal Returns with Corporate Governance as a moderating variable. Corporate Governance proxies are independent commissioners, managerial ownership, and institutional ownership. The population in this study were companies listed on the Indonesia Stock Exchange. Based on the purposive sampling method, 20 samples were obtained and the regression method used was Moderate Regression Analysis (MRA). The results of this study indicate that Employee Stock Options (F-SOs) have a significant effect on Abnormal Returns and Corporate Governance is a moderating variable in the relationship between employee stock options (ESOs) and abnormal returns.